Improved encapsulation capacity of casein micelles with modified structure - Wang, Xiuju; Zhao, Zhengtao (Journal of food engineering, 2022)
Casein micelles (CM) can encapsulate both hydrophobic and hydrophilic bioactive compounds due to their amphiphilic nature. However, the microstructure of CM is sensitive to environmental changes which further influence their encapsulation capacity. Therefore, it is essential to understand their structural changes and their relationship to the encapsulation capacity. This review summarizes the influence of different environmental modification methods on the structure and encapsulation capacity of CM. The encapsulation capacity of CM is improved by increasing the accessibility of targeted compounds (pH cycles, β-casein removal, and enzymatic treatment) or by increasing their binding with the protein matrix (ultrasonication, heating, and homogenization). The combination of the above strategies can be beneficial. A further comprehensive investigation of the binding mechanisms between CM and carried substances and their digestion behavior is essential. This review can provide innovative insights into producing functional ingredients through better utilization of the unique structural properties of CM. •Casein micelles (CM) is a natural and biodegradable carrier of bioactive compounds.•Encapsulation capacity of CM can be enhanced by manipulating its structure.•Binding between bioactive compounds and CM is influenced by environmental changes.•Digestion of compounds can be controlled by changing structure of CM.